Identification of eight novel proteasome variants in five unrelated cases of proteasome-associated autoinflammatory syndromes (PRAAS) - Papendorf, Jonas Johannes; Ebstein, Frédéric; Alehashemi, Sara; Piotto, Daniela Gerent Petry; Kozlova, Anna; Terreri, Maria Teresa; Shcherbina, Anna; Rastegar, Andre; Rodrigues, Marta; Pereira, Renan; Park, Sophia; Lin, Bin; et al. (Frontiers in Immunology, 2023)
Mutations in genes coding for proteasome subunits and/or proteasome assembly helpers typically cause recurring autoinflammation referred to as chronic atypical neutrophilic dermatosis with lipodystrophy and elevated temperatures (CANDLE) or proteasome-associated autoinflammatory syndrome (PRAAS). Patients with CANDLE/PRAAS present with mostly chronically elevated type I interferon scores that emerge as a consequence of increased proteotoxic stress by mechanisms that are not fully understood. Here, we report on five unrelated patients with CANDLE/PRAAS carrying novel inherited proteasome missense and/or nonsense variants. Four patients were compound heterozygous for novel pathogenic variants in the known CANDLE/PRAAS associated genes, PSMB8 and PSMB10, whereas one patient showed additive loss-of-function mutations in PSMB8. Variants in two previously not associated proteasome genes, PSMA5 and PSMC5, were found in a patient who also carried the PSMB8 founder mutation, p.T75M. All newly identified mutations substantially impact the steady-state expression of the affected proteasome subunits and/or their incorporation into mature 26S proteasomes. Our observations expand the spectrum of PRAAS-associated genetic variants and improve a molecular diagnosis and genetic counseling of patients with sterile autoinflammation.